2010
DOI: 10.1137/100782358
|View full text |Cite
|
Sign up to set email alerts
|

Single Phytoplankton Species Growth with Light and Advection in a Water Column

Abstract: Abstract. We investigate a nonlocal reaction-diffusion-advection equation which models the growth of a single phytoplankton species in a water column where the species depends solely on light for its metabolism. We study the combined effect of death rate, sinking or buoyant coefficient, water column depth, and vertical turbulent diffusion rate on the persistence of a single phytoplankton species. Under a general reproductive rate which is an increasing function of light intensity, we establish the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 24 publications
2
73
0
1
Order By: Relevance
“…Before presenting our monotonicity result, we should point out that, in general, λ N 1 (α, D, L) does not enjoy any monotonicity property on either D, α or L. Indeed, Huston et al in [39] showed that, unlike the autonomous case, λ N 1 (α, D, L) is not monotone in D > 0 even when h ≡ 0. In [34], Hsu and Lou proved …”
Section: Theorem 14 Assume That a Is A Positive Constant And H(x T)mentioning
confidence: 98%
See 3 more Smart Citations
“…Before presenting our monotonicity result, we should point out that, in general, λ N 1 (α, D, L) does not enjoy any monotonicity property on either D, α or L. Indeed, Huston et al in [39] showed that, unlike the autonomous case, λ N 1 (α, D, L) is not monotone in D > 0 even when h ≡ 0. In [34], Hsu and Lou proved …”
Section: Theorem 14 Assume That a Is A Positive Constant And H(x T)mentioning
confidence: 98%
“…4 to show that the assertions (ii) and (iii) of Theorem 1.5 remain true. We also mention that though the proof of Theorem 1.5 mainly follows [34], considerable modifications are needed.…”
Section: Theorem 14 Assume That a Is A Positive Constant And H(x T)mentioning
confidence: 99%
See 2 more Smart Citations
“…Major theoretical results include photoacclimation (increase in chlorophyll per cell) (Steele, 1964;Fennel and Boss, 2003), bistability (Yoshiyama and Nakajima, 2002;Ryabov et al, 2010), oscillating SCM (Huisman et al, 2006), hysteresis conditions (Kiefer and Kremer, 1981;Navarro and Ruiz, 2013) and the ESS (evolutionary stable strategy) depth obtained by gametheory approach (Klausmeier and Litchman, 2001;Mellard et al, 2011). Recent mathematical studies solved the persistence and uniqueness of the steady-state solution (Du and Hsu, 2010;Hsu and Yuan, 2010;Du and Mei, 2011) and gave rigorous proofs for the abovementioned ESS depth and the game-theory approach (Du and Hsu, 2008a, b). Additionally, several modeling studies have been conducted to quantitatively assess the importance of different physical-biological processes leading to the SCML (Jamart et al, 1977(Jamart et al, , 1979Varela et al, 1994;Klausmeier and Litchman, 2001;Hodges and Rudnick, 2004;Beckmann and Hense, 2007).…”
mentioning
confidence: 99%